Perbandingan Pemeriksaan antara Kuesioner BCTQ dengan ENMG terhadap Kecepatan Hantar Saraf Pasien Carpal Tunnel Syndrome - Akbar, Julius; Fatimah, Nyimas; Kasim, Bahrun Indawan (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Carpal tunnel syndrome (CTS) is a collection of symptoms such as pain, numbness, tingling, weakness and nocturnal symptoms caused by increased pressure on the carpal tunnel. The examination carried out in determining the severity of CTS is electoneuromyography (ENMG) based on the results of nerve conductivity. BCTQ (boston carpal tunnel questionnare) is also considered capable of assessing the severity based on the symptom severity scale (SSS) and functional status scale (FSS). This study aims to determine the accuracy of the BCTQ questionnaire compared with ENMG on nerve conductivity by using diagnostic test design. The data was collected at Medical Rehabilitation Installation of RSUP dr. Mohammad Hoesin Palembang during October-December 2019 by interviewing the patient’s severity of symptoms and their hand’s function using the BCTQ questionnaire, as well as examining the results of the subject’s ENMG respectively. There were 39 female and 5 male out of 44 study subjects. Bilateral cases 28, right 9 and left 7. The subjects mostly work as housewife. the subjects severity of CTS obtained from SSS, FSS, and ENMG is frequently at the moderate level with the most symptoms of night tingling and the most disrupted function is the function to carry grocery baskets and do household chores. BCTQ which is divided into SSS and FSS has an accuracy value of 70.45% and 72.73% in assessing the severity of CTS. BCTQ is quite accurate as initial screening when compared with the ENMG examination in determining the severity of CTS.